Farmer response to policies promoting organic farming technologies in Finland - Pietola, Kyösti S.; Oude Lansink, Alfons (Oxford University Press, 2001)
This paper analyses factors determining the choice between standard and organic farming technology in Finland by numerically iterating a Bellman eqationg backwards in time. The unknown parameters of a switching-type Probit model are estimated by maximum likelihood estimation. The maximised values of the uncertain revenue streams are simulated. The resultes suggest that decreasing output prices and increasing direct subsidies trigger the switch to organic farming. The switch is also more likely on farms having large land areas and low yields. Intensive livestock production and labour-intensive production decrease the probability of switching to organic farming.
Keywords: Ko; maatilat; maaanviljelijät; luonnonmukainen maataloustuotanto; luonnonmukainen viljely; organic farming; technology choice; dynamic optimisation; switching-type; Probit; Finland